A Novel Bufadiennolide from the Seeds of Mimosa pidica Linn. - N. Yadava, R.; Yadav, Saroj (Asian Journal of Chemistry, 2010)
In the present work, we describe the isolation and characterization of a novel bufadienolide from the seeds of Mimosa pudica Linn.